2010
DOI: 10.1002/jssc.200900571
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of the SPE procedure for determination of pharmaceuticals in water samples by HPLC‐diode array detection

Abstract: This paper focuses on the investigation of different types of SPE sorbents for the preconcentration of eight veterinary pharmaceuticals from water samples. The pharmaceuticals studied were sulfamethazine, sulfadiazine, sulfaguanidine, trimethoprim, oxytetracycline, enrofloxacin, norfloxacin and penicillin G/procaine. Five different SPE materials (Strata-X, Strata-X-C, Strata SDB-L, Strata C8 and Strata C18) from Phenomenex were compared with Oasis HLB with a view to obtaining the best cartridges for all pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…A comparison of data is challenging since either the matrix or the SPE sorbent is not necessarily similar to our study; however, some generalisations can be made. In the case of TRI, ZDV, NVP and CBZ, the results are similar to other studies that have used Strata‐X as sorbent , though, in many cases the matrix has been human plasma . For 3TC, the recovery obtained was better than ours, but the SPE method was optimised for antiviral pharmaceuticals.…”
Section: Resultssupporting
confidence: 85%
“…A comparison of data is challenging since either the matrix or the SPE sorbent is not necessarily similar to our study; however, some generalisations can be made. In the case of TRI, ZDV, NVP and CBZ, the results are similar to other studies that have used Strata‐X as sorbent , though, in many cases the matrix has been human plasma . For 3TC, the recovery obtained was better than ours, but the SPE method was optimised for antiviral pharmaceuticals.…”
Section: Resultssupporting
confidence: 85%
“…Off‐line SPE using HLB was employed in wastewater and river water samples which achieved preconcentration coefficients were 100‐fold for wastewater and 400‐fold for river water. Several studies have used SPE (HLB solid phase) and MeOH as eluent in the monitoring of AMX residues and pharmaceuticals 16, 18–20, 23–29. Similarly to this work, Li et al reported the selection of HLB and MeOH as eluent in the preconcentration of a variety of TPs of penicillin G (PEN G) in wastewater and surface water from a PEN G production facility 8.…”
Section: Resultsmentioning
confidence: 78%
“…Therefore, reversed‐phase extraction is suitable for the experiment. Strata‐X, which is applied to the reversed‐phase extraction, is a surface‐modified styrene skeleton with a pyrrolidone group, whose retention mechanisms are hydrophobic, hydrogen‐bonding and aromatic (Mutavdzic Pavlovic et al ., ). From the structure of the nalbuphine (hydroxyl, benzene and fat‐soluble), the retention mechanisms of strata‐X are very suitable for the extraction of nalbuphine.…”
Section: Resultsmentioning
confidence: 97%